Approach for application-specific selection of risk assessment methods - Lukas Nikelowski; Rika Voss (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: The field of risk assessment contains many methods for evaluating risks. For companies who face the need of dealing with risks, the large number of methods might be confusing and overwhelming. This paper helps to introduce companies to the existing methods and its different requirements as well to support the application-specific selection of a risk assessment method. Methodology: A systematic literature review regarding existing risk assessment methods is executed using the following identification terms: 1. 'risk assessment' AND (method OR technique OR instrument OR tool OR process) AND 'supply chain' 2. 'risk analysis' AND (method OR technique OR instrument OR tool OR process) AND 'supply chain'. Used databases are EBSCOhost, Scopus, and Web of Science. Findings: 194 sources containing relevant content on the methods of risk assessment are identified. 138 sources are published as journal articles and 56 sources as conference contributions. The main result is a classification and an application-specific selection procedure for risk assessment methods. Originality: This publication enables a comprehensive comparison and evaluation of existing risk assessment methods. It further supports the decision-making by presenting an overview and a selection procedure for choosing an application-specific method.
urn:nbn:de:gbv:830-882.0161927; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Supply Chain Risk Management; Supply Chain Security